2017
DOI: 10.1021/acs.energyfuels.7b01001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Methane Content on the Water–Oil Interface: Insights from the Molecular Level

Abstract: The interfacial tension (IFT) is an important factor for the hydrocarbon flow in a porous reservoir. Methane, one main accompanied gas of hydrocarbon, has a crucial influence on the IFT. However, the methane effect is still unclear. In this work, the effects of the methane content, temperature, and pressure on the water−oil interface were investigated, employing molecular dynamics simulations. The interfacial density profiles were given and indicated that the methane molecules accumulate at the interface, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…The system sizes used here ensure that the finite-size effects are negligible. 38,[40][41][42][43][72][73][74] Each system was equilibrated for 5 ns in the NPT ensemble (only L z varied) and we ran a 5 ns production under NVE conditions. The temperature was controlled using the Nose ´-Hoover thermostat and pressure using the Parrinello-Rahman barostat.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…The system sizes used here ensure that the finite-size effects are negligible. 38,[40][41][42][43][72][73][74] Each system was equilibrated for 5 ns in the NPT ensemble (only L z varied) and we ran a 5 ns production under NVE conditions. The temperature was controlled using the Nose ´-Hoover thermostat and pressure using the Parrinello-Rahman barostat.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Experiments, [25][26][27][28][29][30][31][32][33][34][35][36][37] theory, [32][33][34][36][37][38][39] and simulations [38][39][40][41][42][43][44][45] have been successfully employed to understand the bulk and interfacial properties of alkane + water + CH 4 /CO 2 systems. These studies have reported the occurrence of, for example, a two-phase region at high pressures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…de Lara et al explored the structural and dynamic properties of crude oil at the molecular level, and their calculations suggest an increase in fluid diffusivity of the oil phase with the IFT reduction [24]. More recently, the effects of methane on the water/octane interface were studied by molecular modeling, which showed that enlarging the ratio of methane could increase the interfacial roughness and interfacial thickness of the water/oil interface [25]. However, although researchers have studied the microstructure of the interface and the change of the IFT with MD simulation providing molecular information and insights, little work reported how to estimate the MMP of CO 2 injected into crude oil by MD simulation and understand the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%